Análisis de las estrategias de marketing de la empresa Centro Comercial Aguirre ubicado en la ciudad de Babahoyo en el periodo 2023 - Amaiquema Pilay, Nayeli Odalys (2025)
This case study contextualizes its research in the Aguirre Shopping Center, located in the city of Babahoyo, specifically on the streets of 27 de Mayo between 5 de Junio and García Moreno, dedicated to the sale of household appliances and furniture. For years it has been developing its commercial activity in the midst of a very competitive market environment. The main objective was to analyze the marketing strategies used by the Aguirre Shopping Center in the city of Babahoyo during the period 2023, identifying its effectiveness for the recommendation of strategies that contribute to the sustainability of the company. The case study is based on the inductive method with a descriptive characteristic and with a mixed modality: qualitative - quantitative, since theoretical conclusions are established based on the interview and results of the information collected from the target market are also presented. This research methodology is aimed at establishing the behavior of the variable: marketing strategy. The results showed that the Aguirre Shopping Center has maintained a customer portfolio that has not been evaluated on its level of satisfaction through any formal process and that its main strategies were: good customer service and the use of social networks such as Facebook and Instagram. It was possible to demonstrate the perception of customers on the product variable where 49% stated that it is a factor that should be improved in the company, on the price variable 63% of them think that, if they are competitive in relation to other companies, on the advertising variable 95% of customers do not give importance to these networks because they are not constantly updated and they think that they need to be strengthened.